Diseño de un modelo de costeo abc enfocado al fortalecimiento de los productos de captación en la Cooperativa de Ahorro y Crédito Guaranda Ltda. provincia Bolívar, cantón Guaranda año 2019 - Espín Mantilla, Freddy Jair (2020)
determination of costs is achieved since more certain values are obtained than in other cost systems, values are established for each activity, these activities for more than not have greater impact generate costs. Every financial entity needs a cost system since with it the actual costs of each product are determined, this helps the company to grant an appropriate sales cost to its customers. If adequate cost control is achieved for each activity within an organization, more accessible products will be offered to customers, since there is a more efficient cost structure, with the ABC costing method a better cost optimization will be achieved without losing product quality. This also allows the savings and credit cooperative Guaranda Ltda., To measure the impact that the application of an ABC cost system will have, in such a way that with the application of the same, the costs will be reduced and subsequently processed to obtain a better profitability within the cooperative With the application of this activity-based ABC costing model, a better procedure will be achieved for each collection product, detailing the activities that generate value within each process, determining which process has the highest and lowest cost. With the determination of the costs for each activity, efficient information will be obtained, which will be used by management to make the decision-making process efficiently. Key words: Cost ABC, Cost-Driver, Activity, PAY BACK.